Mechanisms of palmitate-induced lipotoxicity in osteocytes (2019)
Background: Lipotoxicity is defined as cellular toxicity observed in the presence of an abnormal accumulation of fat and adipocyte-derived factors in non-fat tissues. Palmitic acid (PA), an abundant fatty acid in the bone marrow and particularly in osteoporotic bones, affects osteoblastogenesis and osteoblast function, decreasing their survival through induction of apoptosis and dysfunctional autophagy. In this study, we hypothesized that PA also has a lipotoxic effect on osteocytes in vitro. Methods: Initially, we tested the effect of PA on osteocyte-derived factors DKK1, sclerostin and RANKL. Then, we tested whether PA affects survival and causes apoptosis in osteocytes. Subsequently, we investigated the effect of PA on autophagy by detecting the membrane component LC3-II (Western blot) and staining them and lysosomes with Lysotracker Red dye. Results: PA decreases RANKL, DKK1 and sclerostin expression in osteocytes. In addition, we found that PA induces apoptosis and reduces osteocyte survival. PA also caused autophagy failure identified by a significant increase in LC3-II and a reduced number of autophagosomes/lysosomes in the cytoplasm. Conclusion: In addition to the effects of PA on RANKL, DKK1 and sclerostin expression, which could have significant deleterious impact on bone cell coupling and bone turnover, PA also induced apoptosis and reduced autophagy in osteocytes. Considering that apoptosis and cell dysfunction are two common changes occurring in the osteocytes of osteoporotic bone, our findings suggest that PA could play a role in the pathogenesis of the disease. Suppression of these effects could bring new potential targets for therapeutic interventions in the future.